Yellow fever virus investigation in tissues of vampire bats Desmodus rotundus during a wild yellow fever outbreak in Brazilian Atlantic Forest. (October 2022) - Cupertino, Marli do Carmo; Bayão, Taciana de Souza; Xisto, Mariana Fonseca; Paula, Sérgio Oliveira; Ribeiro, Susana Puga; Montenegro, Stefania Salvador Pereira; Freitas, Mariella Bontempo; Gomes, Andréia Patrícia; Siqueira-Batista, Rodrigo
Abstract: In the last decade a large outbreak of Yellow Fever (YF) has been observed in Brazilian Atlantic Forest region, traditionally a non-endemic area. In this scenario, the role of wild mammal species as YF reservoirs can be questioned, especially the hematophagous bat, Desmodus rotundus . So, the objective of this study was to analyze molecularly the presence of the YF virus (YFV) in hematophagous bats during a YF outbreak in Brazil. Twenty-one samples were collected from seven adult male hematophagous bats D . rotundus . As YFV is considered a viscerotropic and neurotropic virus, samples of liver, kidney and brain were collected and molecularly analyzed using the RT qPCR technique. The animals were captured according to ethical protocols during a YF outbreak in Brazil in 2017, from a region of the Brazilian Atlantic Forest. The results revealed that the analyzed tissue samples were not infected with the YFV. The negative results for this bat species allow us to infer that other animals may be reservoirs of this virus in this ecosystem and they probably have not been identified yet. Therefore, health surveillance actions are essential to monitor the role of wild animals in the YF dissemination in Brazilian Atlantic Forest and alert to the possibility of new geographic amplification of areas where YF occurs. This research encourages the new search about the role of wild animals on YFV transmission and reinforces the importance of epidemiological surveillance in the transmission of human infectious diseases. Highlights: This is the first investigation of yellow fever virus (YF) in Desmodus rotundus vampire bats during an outbreak of wild YF. The negative results point to the need to research animals in this biome that may be involved in the YF cases redistribution. Health surveillance actions should be encouraged to identify wild animals involved in the maintenance of arbovirus cycles.